PELATIHAN PEMBUATAN POP UP BOOK SEBAGAI MEDIA PEMBELAJARAN MATEMATIKA DI MTS MAFATIHUL HUDA PUJON - Dian Fitri Argarini; Nurcholis Sunuyeko; Rochsun Rochsun; Lutfi Mukaromatun Nisa (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2023)
Mathematics subjects are often considered difficult for students, especially junior high school students who have very lit t le emotion, not infrequently these students also regard mathematics as a fr ightening specter when the learning process takes place. Learning media as a tool that ca n help the teaching and learning process to achieve learning objectives that are effective and fun. One of the learning media that can be made with simple and inexpensive equipment for junior high school students is Pop up book media. The pop- up book media it self is a three- dimensional or 3D learning media where when the book is opened, pictures or writings appear that appear very interesting according to the material to be taught. This media tends to make students more interested in learning it and forget a lit t le about the difficulties and fears of mathematics.